THE ROLE OF KNOWLEDGE BUILDING DISCOURSE TO ENHANCE STUDENTS’ CURIOSITY IN INQUIRY BASED CLASSROOM - Martina Mulyani (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
Curiosity has been identified as driving force in doing an inquiry and one most important spur to educational attainment. As 2013 curriculum emphasizes the implementation of Inquiry Based Learning, teachers as curriculum executors should stimulate their students’ curiosity. The study is aimed to investigate if Knowledge Building Discourse (KBD) is able to develop students’ curiosity. The study was conducted in one private university in Cimahi. 25 junior students participated in this research. The study can be included into Second/Foreign Language Classroom Research. Classroom Research was employed to reveal the strength of KBD by identifying the students’ and teacher’s interaction in the classroom discourse. The study utilized rank scale to analyze spoken discourse from Sinclair and Coulthard (1992). In addition, the questionnaires were used to highlight the students’ opinion towards KB. The result of the study shows that through KBD, the students are able to search and share information to the class rather than provide information to the class for the sake of answering the teacher’s elicitation. It means, the implementation of KBD in classroom can enhance students’ curiosity as KBD can produce discourse that allows students’ inquiry to take place. Eventually, KB can be applied in 2013 curriculum which highlights Inquiry Based Learning in its teaching learning process.